2019
DOI: 10.3390/nu11020236
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malnutrition in Pediatric Hospitals in Developed and In-Transition Countries: The Impact of Hospital Practices

Abstract: Presently, undernutrition still goes undetected in pediatric hospitals despite its association with poor clinical outcomes and increased annual hospital costs, thus affecting both the patient and the health care system. The reported prevalence of undernutrition in pediatric patients seeking care or hospitalized varies considerably, ranging from 2.5 to 51%. This disparity is mostly due to the diversity of the origin of populations studied, methods used to detect and assess nutritional status, as well as the lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
19

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 89 publications
3
57
0
19
Order By: Relevance
“…Failure to accurately diagnose PMN leads to increased costs due to longer length of stay, increased rates of complications and infection, higher mortality rates, and impaired cognitive development. [1][2][3][4][5][6][7][8][9][10][11][12] It impedes research with inaccurate and ill-defined terms such as failure to thrive and inconsistent criteria used among studies. 13 Survey results indicated respondents knew that some or most of the coding and billing staff in their facilities were aware of the PMN recommended indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to accurately diagnose PMN leads to increased costs due to longer length of stay, increased rates of complications and infection, higher mortality rates, and impaired cognitive development. [1][2][3][4][5][6][7][8][9][10][11][12] It impedes research with inaccurate and ill-defined terms such as failure to thrive and inconsistent criteria used among studies. 13 Survey results indicated respondents knew that some or most of the coding and billing staff in their facilities were aware of the PMN recommended indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Al comparar estas cifras con las identificadas por otros estudios realizados en países fuera de Latinoamérica, fue posible identificar cifras similares; una revisión que reunió datos de prevalencia de desnutrición de 15 países europeos y 2 estudios realizados en Canadá mostró para el indicador P/T, un rango entre 9 y 14,8%, usando como parámetro el encontrarse por debajo de dos desviaciones estándar 44 .…”
Section: Estancia Hospitalariaunclassified
“…Lo anterior, pone en claro que el bajo peso para la talla a nivel hospitalario es un problema multifactorial, que, si bien es preocupante en países de recursos bajos debido al acceso limitado de alimentos o atención médica, también puede desencadenarse por otras causas como enfermedades en países en transición 44,48 .…”
Section: Estancia Hospitalariaunclassified
“…When criteria other than the Academy/ASPEN consensus statement criteria have been used, the prevalence of pediatric malnutrition in US hospitals has varied widely. One summary reported rates between 2.6% and 24.5%, whereas others have reported rates between 6% and 51% . Bierman and colleagues reported that 30% of patients admitted to the pediatric ICU or pediatric unit were identified with PCM using the Academy/ASPEN consensus statement criteria (n = 1532), but only 33% of those were actually coded with PCM …”
Section: Prevalencementioning
confidence: 99%